Comparative availability of edible mushrooms in the highlands and lowlands of Chiapas, Mexico, and its implications in traditional management strategies - Ruan-Soto, Felipe; Cifuentes Blanco, Joaquín; Garibay Orijel, Roberto; Caballero Nieto, Javier (Instituto de Ecología, A.C., 2020)
Background and Aims: Wild edible mushroom traditional management strategies have been described for both highlands and lowlands in Mexico. It seems that, in the lowlands, the usage of this resource is lower than in the highlands. Ecological ethnomycology is concerned with understanding how certain ecological patterns in mushrooms influence traditional management strategies. In this study we present a comparison between the edible mushrooms’ fruit body availability in two distinct ecological units: The Highlands of Chiapas and the Lacandon Rainforest. Our hypothesis was that the fruit body availability is higher in both the highlands and preserved vegetation, which might explain a greater usage in these ecosystems, as well as the opportunistic usage of mushrooms in the lowlands.Methods: During 2009 and 2010, we monitored the fruit body abundance, biomass, spatial and temporal frequencies, as indicators of edible mushroom availability in rectangular transects in three sites per ecological setting (highlands/lowlands) both in preserved vegetation sites and agroecosystems in Chiapas, Mexico.Key results: In the highlands, a greater richness (35 ethnotaxa) and biomass production (12,345.2 g) was recorded, but the lowlands yielded a greater number of fruit bodies (3212) and a higher spatial and temporal frequency (76.6% and 40% respectively).Conclusions: In both ecological settings, edible mushroom availability allow their use; however, it has different ecological traits. This may explain why, in the highlands, people use a more diverse array of species and prefer those of greater biomass. Contrastingly, in the lowlands less species are used, but they are more abundant and have a greater spatial and temporal frequency. Our data demonstrate that the lowlands and agroecosystems are spaces with edible mushroom availability comparable to that of highland forests.